Hubungan Antara Hardiness Dengan Kesiapan Kerja Pada Mahasiswa Psikologi Islam IAIN Kediri Angkatan 2018 - Fidia, Astuti; Nur Kholifah, Anis; Sunarno, (Happiness: Journal of Psychology and Islamic Science, 2022)
Abstract : Students as graduates from universities certainly have more knowledge and skills than the lower levels. However, this does not require that students be ready for the world of work. Students still feel anxious and lack confidence in the world of work, even though they are in the final semester and will graduate from college. If this condition is continued, students will have difficulty competing in the world of work later. Therefore, students may need tough conditions themselves that help to overcome obstacles in themselves as well as obstacles in the world of work, this tough condition is called hardiness. The purpose of this study is to determine the level of hardiness and the level of work readiness as well as to determine the relationship between hardiness and job readiness in Islamic Psychology students of IAIN Kediri class 2018. The subjects of this study amounted to 97 students of Islamic Psychology IAIN Kediri class 2018. As for the sampling technique, Researchers used a non-probability technique, namely accidental sampling. Furthermore, for data processing using the SPSS 20 for windows application using descriptive statistical analysis methods of frequency and non-parametric statistics with Spearman Rho hypothesis testing. Based on this research, it was found that the average student's hardiness level was in the medium category, amounting to 45.4%. The level of student work readiness is in the medium category average of 47.4%. Based on the results of the analysis of Spearman Rho, a score of 0.802 was obtained with a significance value (2 tailed) of 0.000. This statement can be interpreted as Ha is accepted and Ho is rejected. Then the correlation value is positive and has very strong criteria, which means that the relationship between hardiness and work readiness is 0.802 and has very strong criteria. Kay word: Hardiness, Working readiness, students.